PENGARUH BUDAYA ORGANISASI DAN KOMPENSASI TERHADAP KINERJA PEGAWAI DI RSUD SITI AISYAH LUBUKLINGGAU - Dwi Wageanto; Sardiyo Sardiyo (LPPM UNIVERSITAS BINA INSAN, 2018)
This study is related to the influence of organizational culture and compensation for employee performance at Siti Aisyah Hospital in Lubuklinggau, the purpose of this study is to determine the effect of organizational culture on performance partially, the effect of compensation on performance partially. The influence of organizational culture and compensation for performance simultaneously. The number of samples used as many as 100 people using the population research theory in taking samples, data collection was done using a questionnaire method. The data analysis technique used was an analysis using Statistical Product and Serving Solution (SPSS). The results of the study found that the variables of organizational culture and compensation simultaneously affect performance, this can be seen from the value of Fcount = 136,482> Ftable = 3,09 with a significant level of sig = 0,000 <α = 0,05. As well as organizational culture variables significantly influence employee performance, this can be seen from the value of t-count 3.914> t-table 1.66 and sig value 0.000 <0.05. And compensation variables significantly influence employee performance. This can be seen from the t-count value of 4,053> t-table 3,000 and sig value 0,000 <0,05.